Reserve Accumulation Is Prioritized Over Growth Following Single or Combined Injuries in Three Common North American Urban Tree Species - Ramirez, Jorge Andres; Vitali, Valentina; Martínez-Vilalta, Jordi; Handa, I. Tanya; Messier, Christian (Frontiers in Plant Science, 2021)
Trees that grow in urban areas are confronted with a wide variety of stresses that undermine their long-term survival. These include mechanical damage to the crown, root reduction and stem injury, all of which remove significant parts of plant tissues. The single or combined effects of these stresses generate a complex array of growth and ecophysiological responses that are hard to predict. Here we evaluated the effects of different individual and combined damage on the dynamics of non-structural carbohydrates (NSC, low weight sugars plus starch) concentration and new tissue growth (diameter increment) in young trees. We hypothesized that i) tissue damage will induce larger reductions in diameter growth than in NSC concentrations and ii) combinations of stress treatments that minimally alter the ‘functional equilibrium’ (e.g., similar reductions of leaf and root area) would have the least impact on NSC concentrations (although not on growth) helping to maintain tree health and integrity. To test these hypotheses, we set up a manipulative field experiment with 10-year-old trees of common urban species (Celtis occidentalis, Fraxinus pennsylvanica, and Tilia cordata). These trees were treated with a complete array of mechanical damage combinations at different levels of intensity (i.e., three levels of defoliation and root reduction, and two levels of stem damage). We found that tree growth declined in relation to the total amount of stress inflicted on the trees, i.e., when the combined highest level of stress was applied, but NSC concentrations were either not affected or, in some cases, increased with an increasing level of stress. We did not find a consistent response in concentration of reserves in relation to the combined stress treatments. Therefore, trees appear to reach a new ‘functional equilibrium’ that allows them to adjust their levels of carbohydrate reserves, especially in stems and roots, to meet their metabolic demand under stressful situations. Our results provide a unique insight into the carbon economy of trees facing multiple urban stress conditions in order to better predict long-term tree performance and vitality.